2022
DOI: 10.12997/jla.2022.11.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Genetic Associations Between the Use of Statins and Alzheimer's Disease

Abstract: Objective Alzheimer's disease (AD) is the most common cause of dementia. The statins have shown beneficial effects on cognitive functions and reduced the risk of dementia development. However, the exact mechanisms of statin effects in AD are not yet fully understood. In this study, we aimed to explore the underlying mechanisms of statin on AD. Methods We downloaded AD blood dataset (GSE63060) and statin-related blood gene expression dataset (GSE86216). Then we performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…The results indicated that four genes including the ABCG1 gene were associated with both diseases 124 . Genomic data from AD shows that ABCG1 expression is upregulated while taking statins reduced ABCG1 expression in the blood of AD patients 125 . Table 1 summarizes ABCG1's effects on AD.…”
Section: Abcg1 In Admentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that four genes including the ABCG1 gene were associated with both diseases 124 . Genomic data from AD shows that ABCG1 expression is upregulated while taking statins reduced ABCG1 expression in the blood of AD patients 125 . Table 1 summarizes ABCG1's effects on AD.…”
Section: Abcg1 In Admentioning
confidence: 99%
“…124 Genomic data from AD shows that ABCG1 expression is upregulated while taking statins reduced ABCG1 expression in the blood of AD patients. 125 Table 1 summarizes ABCG1's effects on AD. In humans, the ABCG1 gene resides on chromosome 21 suggesting that it may have a role(s) in Down syndrome (DS) pathology.…”
Section: Abcg1 In Admentioning
confidence: 99%
“…Therefore, the prediction of drug-related adverse events in a specific patient, appropriate drug selection, and avoidance of adverse events are expected to improve drug adherence and clinical outcomes. With recent advances in genetic research [8], several genome-wide association studies (GWASs) have reported genetic loci associated with ACEI-related cough. Candidate genes include NTSR1 [9], NELL1 [10], and CLASP1 [11].…”
mentioning
confidence: 99%